STUDI MINAT BEKERJA DAN MINAT MELANJUTKAN KE JENJANG PENDIDIKAN YANG LEBIH TINGGI MAHASISWA IST-PI MAKASSAR - Dian Mahdiansah (STKIP Andi Matappa Pangkep, 2019)
The purpose of the research was to know the difference between students who have interest to work and students who have interest to continue the higher education level of Makassar IS-PI students. This research was a comparative one and the population were taken from the students of civil engineering and electrical engineering of IST-PI of Makassar. The amount of sample is 25 students from civil engineering and 25 students from electrical engineering which was chosen randomly. Thus, the amount of this research sample was 50 students. The data was collected by questionnaire. The analysis of research that were used were descriptive statistics and inferential. The result after counting showed th 4.5 and tt 2.1, in significant level it was 0.05 or 5% and dk 98 because th was higher than tt. Thus ha was accepted and ho was denied. It means that there are differences between students of civil and electrical engineering of IST-PI who have interest in working and students who have interest in continuing the study to a higher level.